Design and Research of Intelligent Educational Administration Management System Based on Mobile Edge Computing Internet - Lizhu Dai (Hindawi Limited, 2021)
Educational administration management is the primary link in the teaching management of colleges and universities. Mobile edge computing can create a carrier-class service environment with high performance, low latency, and high bandwidth and accelerate the rapid download of various contents, services, and applications in the network, which greatly promotes the upgrade of the educational administration system. Using educational administration management system to manage educational administration can promote the teaching work of colleges and universities better. This paper aims to design and develop a set of educational management information systems, using mobile edge computing (MEC) technology to combine the IT service environment and cloud computing technology at the edge of the network to improve the computing and performance of the edge network. Storage capacity reduces network operation and service delivery delay, improves user service quality experience, and helps universities improve the efficiency of educational administration management. This paper first discusses the implementation mode and related technologies of educational administration management system, then discussing the demand analysis of each functional module of the system; in the nonfunctional demand analysis part, the system needs to meet the security and performance. According to the function modules included in the system, using the way of running interface screenshot, implementation code, and flowchart, the paper analyzes the realization process of the function module and also completes the function test of the function module, as well as the performance test of the whole system. The experimental results show that the rule 4 of teaching level evaluation data mining reveals that the support degree of excellent teaching effect is 18% and the confidence degree is 53% in the age of 50–60. Rule 5 shows that the degree of support is 16% and the degree of confidence is 52%. Rule 10 shows that the degree of support for excellent teaching effect is 22% and the confidence level is 71%. The high confidence level of backbone teachers aged 50–60 indicates that the old teachers are more experienced and popular with students, while the young teachers under 30 need to focus on training to help young teachers improve their professional level. From the above data, it can be seen that through the application of mobile edge technology the educational administration system is more efficient in processing and analyzing data in terms of teacher management and teaching level, which once again shows the impact of this network technology on the construction and development of educational administration systems highly feasible.